“The Influence of Academic Education on Crime Rate within South Asia”: A Case Study from Pakistan - Zafar, Fareeha; Butt, Moazzam; Munir, Sumaira; Arif, Sobia (Advances in Social Sciences Research Journal, 2017)
This paper illustrates effects of academic education on the crime ratio prevailing in the South Asian countries. The study introduces practical impacts amongst crime and education in South Asian countries and particularly in Pakistan, utilizing different information sources. The paper shows positive relationship between education and crime. The result demonstrates that in the Pakistan there are not enough opportunities available to accommodate the educated people. The empirical evidences indicate that the criminal activities raises the financial benefits more than those opportunities offered to the educated people. This study concludes that if private and public sector provide sufficient opportunities to adjust all the educated people can yield significant social advantages and can be a key approach device in the drive to diminish crime